A syntactic approach to the Spanish ’al + infinitive’ construction - Rico, Pablo (Borealis – An International Journal of Hispanic Linguistics, 2016)
The paper seeks to study the way in which the interpretation is fixed in the Spanish AL + infinitive construction. The reading of these adjuncts can be temporal or causal. Some studies that have approached this issue previously (Rigau 1993; Alonso-Ovalle 2002) have attributed the interpretative disparity to purely semantic reasons, while others (Rigau 1995; Hernanz 1999; Martines 2000) have described the phenomenon without delving too deep in the syntactic details that influence the reading. The aim of this analysis is to approach the problem of the interpretation considering factors of syntactic order. I will claim that the reading is fixed depending basically on two factor: 1) the kind of topological relation that is established in each case: in temporal adjunction, the C head selects an IP as its ground; on the contrary, in the causal adjunction the ground is an XP, a projection between IP and CP that generates opacity with regard to the reading of the temporality; and 2) the retrospective orientation that the auxiliary haber generates.